Ectoparasites of avian species visiting selected fruit orchards of Davao City, Mindanao Island, Philippines - Elsa May Delima-Baron; Marian Dara T. Tagoon; Lyre Anni E. Murao (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ectoparasites are essential in disease transmission on several hosts, including avian species. Studies on ectoparasites of birds in various habitats are substantial. However, this study was conducted to add to the minimal information about bird ectoparasites in fruit orchards. Birds were captured via mist netting in two preselected fruit orchards and dusted afterward for ectoparasite collection before release. Ectoparasites were identified based on their morphological features. Twenty-eight avian species (N=468 individuals of birds), 25% of which were Philippine endemic, were recorded in the surveyed fruit orchards. Nine species (N=24 individuals) were captured, all of which are known to occur in areas near human settlements. Ectoparasites were collected from feather dustings of 12 captured non-breeding individuals representing five of the nine bird species. The abundance, as well as the type of ectoparasites among captured birds, varied among bird species. An individual of Todiramphus chloris (white-collared kingfisher) had a heavy infestation. A total of 1618 adult ectoparasites were collected: 11 mites (9 identified to species level, two identified to genus level only), one species of flea, and eight louse (seven identified to species level, one identified to genus level only). Most ectoparasites collected were feather mites (order Acari, suborder Astigmata, family Analgoidea) and chewing lice (order Phthiraptera). Data revealed that despite a high degree of disturbance, fruit orchards do harbor and allow the existence of several birds, including endemic species. Despite the low capture rate, most bird individuals were infested with ectoparasites. This data reiterates previous reports that wild birds are important hosts of several ectoparasites including those found in fruit orchards.